Further generalization of generalized quasilinearization method. (1994) - Lakshmikantham, V.; Shahzad, N.
Abstract : The question whether it is possible to develop monotone sequences that converge to the solution quadratically when the function involved in the initial value problem admits a decomposition into a sum of two functions, is answered positively. This extends the method of generalized quasilinearization to a large class.